Percutaneous access of an intraoperatively recanalized mid-superficial femoral artery for distal lower limb revascularization - Angelos Karelis, MD, PhD; Doriana Ferrara, MD; Björn Sonesson, MD, PhD; Nuno Dias, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
A 61-year-old male patient presented with rest pain and ulceration in his left leg 1 week after a hybrid procedure with bilateral external iliac stenting, common femoral artery thromboendarterectomy, and left-sided femoral popliteal bypass with an in situ saphenous vein. The bypass had been stented intraoperatively but had again become occluded directly after surgery. In the present report, we demonstrate the usefulness of direct percutaneous access to the mid-superficial femoral artery that had been intraoperatively recanalized via brachial artery access during the same procedure. This innovative combination of approaches allows for proximal and distal lower limb revascularization with stenting when avoidance of femoral artery access is considered appropriate.